Critical concepts in international relations - Edkins, Jenny (Routledge, 2014)
To help users navigate and make sense of such an enormous, growing-and ever more complex-corpus of scholarship, Routledge is pleased to announce this new four-volume collection edited by Jenny Edkins. 'Critical International Relations' answers the need for a one-stop reference resource to enable scholars and students readily to acquaint themselves with key themes and contributions that typify the use of critical approaches to International Relations in diverse temporal and geographical locations. Much more than a historical survey of the field, or a simple assembly of works that may be regarded as "canonical", the editor has brought together an innovative compilation of materials to reflect the vibrancy and excitement of Critical International Relations. And, in addition to those relatively new to the field who will especially benefit from this enterprise, the collection will also be welcomed by established researchers from across the disciplinary spectrum who are currently engaged in critical work on International Relations